Les ressources éducatives libres et les archives ouvertes dans le mouvement du libre accès - Sihem Zghidi; Mokhtar Ben Henda (Centre National d'Enseignement à Distance, 2020)
Since its emergence in the 90s as a global movement, the world of openness has continued to generate clones. The Open Archives initiative (OAI) and the movement of Open Educational Resources (OER) constitute nowadays two essential streams of free transmission and open access to knowledge. OER, as a "derived" product of Open Archives, using the same tools and approaches, is still seeking for a better maturity, both at technical and strategical levels. From our own perspective, alignment with a better-functioning governance model of open archives would certainly be advantageous to OER, but it will also be appropriate for them to cultivate their own identity. The relations between both movements are still subject to controversies that we intend to explore from educational and scientific standpoints.